Digital Environments Ethnographic Perspectives Across Global Online and Offline Spaces - Fromming, Urte Undine; Kohn, Steffen; Fox, Samantha; Terry, Mike (transcript Verlag, 2017)
Digital technology already has permeated the physical world. Devices such as smartphones, tablets or wearables and online venues like virtual worlds and social networks have penetrated every part of our lives. The contributions to this volume apply innovative forms of ethnographic research to the digital realm. They examine the emergence of new online communities around Greenlandic news blogs or Malaysian LGBT Facebook groups, the rise of transnational migrant networks facilitated by social media, or the representation of conflicts and the proliferation of ideologies within online spaces.
Description based on print version record.
KU Select 2016 Front List Collection
Keywords: Social Science / Media Studies; Language Arts & Disciplines / Communication Studies; Social sciences; Electronic books